Live and heat-killed Lactobacillus reuteri reduce alveolar bone loss on induced periodontitis in rats - Moraes, Renata M. [UNESP]; Lescura, Carlos Matheus; Milhan, Noala V.M.; Ribeiro, Jaqueline L.; Silva, Francielly A.; Anbinder, Ana Lia (Elsevier, 2020)
Objective Lactobacillus reuteri is reported as a beneficial adjunct to conventional periodontitis treatment or as monotherapy for gingivitis in several clinical trials. However, probiotics are not free from the risk of adverse effects. We investigated the effects of live and heat-killed (paraprobiotic) L. reuteri during the development of ligature-induced periodontitis in rats. Methods Thirty-two male rats were divided into four groups—control group: healthy rats, LIP group: rats with ligature induced periodontitis, LIP/PRO group: rats with periodontitis that received live L. reuteri, LIP/PARA group: rats with periodontitis that received heat-killed L. reuteri. Treatment was administered for 30 days prior to ligation and continued for 14 days until euthanasia. The hemimandibles were removed and submitted to radiographic analysis, microcomputerized microtomography (μCT) and histomorphometric analysis. Results Radiographic analysis revealed that pro- and paraprobiotics enhanced the percentage of mesial bone support. The μCT analysis showed that paraprobiotic treatment increased bone volume and trabecular number while decreasing total bone porosity and trabecular separation. Live probiotic led to higher trabecular thickness. In the histomorphometric analysis, paraprobiotics significantly prevented furcation bone loss and collagen breakdown, although both pro- and paraprobiotics similarly reduced mesial bone loss. There were no significant differences in attachment loss or the number of tartrate-resistant acid phosphatase -positive cells across treatments. Conclusions Although viable and heat-killed bacteria reduced mesial alveolar bone loss and ameliorated furcation microarchitecture parameters, paraprobiotics presented the most pronounced results preventing periodontitis development. This can contribute to the future use of paraprobiotics in the prevention and treatment of periodontitis.
Keywords: Experimental periodontitis; Host modulation therapy; Probiotics